ILRI's WILD women—Women In Livestock Development—are celebrating International Women's Day 2020 - International Livestock Research Institute (International Livestock Research Institute, 2020)
The film highlights a few Women In Livestock Development (WILD) who work at the International Livestock Research Institute (ILRI).